Immunoglobulin M-degrading enzyme of Streptococcus suis (IdeSsuis) impairs porcine B cell signaling - Breitfelder, Annika Katharina; Schrödl, Wieland; Rungelrath, Viktoria; Baums, Christoph Georg; Alber, Gottfried; Schütze, Nicole; Müller, Uwe (Frontiers in Immunology, 2023)
Streptococcus suis (S. suis) is an important porcine pathogen, causing severe disease like meningitis and septicemia primarily in piglets. Previous work showed that the IgM-degrading enzyme of S. suis (IdeSsuis) specifically cleaves soluble porcine IgM and is involved in complement evasion. The objective of this study was to investigate IdeSsuis cleavage of the IgM B cell receptor and subsequent changes in B cell receptor mediated signaling. Flow cytometry analysis revealed cleavage of the IgM B cell receptor by recombinant (r) IdeSsuis_homologue as well as IdeSsuis derived from culture supernatants of S. suis serotype 2 on porcine PBMCs and mandibular lymph node cells. Point-mutated rIdeSsuis_homologue_C195S did not cleave the IgM B cell receptor. After receptor cleavage by rIdeSsuis_homologue, it takes at least 20 h for mandibular lymph node cells to restore the IgM B cell receptor to levels comparable to cells previously treated with rIdeSsuis_homologue_C195S. B cell receptor mediated signaling after specific stimulation via the F(ab')2 portion was significantly inhibited by rIdeSsuis_homologue receptor cleavage in IgM+ B cells, but not in IgG+ B cells. Within IgM+ cells, CD21+ B2 cells and CD21- B1-like cells were equally impaired in their signaling capacity upon rIdeSsuis_homologue B cell receptor cleavage. In comparison, intracellular B cell receptor independent stimulation with tyrosine phosphatase inhibitor pervanadate increased signaling in all investigated B cell types. In conclusion, this study demonstrates IdeSsuis cleavage efficacy on the IgM B cell receptor and its consequences for B cell signaling.